Executive pay and “independent” compensation consultants - Murphy, Kevin J.; Sandino, Tatiana (Journal of Accounting and Economics, 2010)
Executive compensation consultants face potential conflicts of interest that can lead to higher recommended levels of CEO pay, including the desires to “cross-sell” services and to secure “repeat business.” We find evidence in both the US and Canada that CEO pay is higher in companies where the consultant provides other services, and that pay is higher in Canadian firms when the fees paid to consultants for other services are large relative to the fees for executive-compensation services. Contrary to expectations, we find that pay is higher in US firms where the consultant works for the board rather than for management.